2009
DOI: 10.1007/s12663-009-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Keratocystic odontogenic tumor: a review

Abstract: The odontogenic keratocyst is a very well known odontogenic cyst. There are many types of cysts of the jaws, but what makes the odontogenic keratocyst unusual are its characteristic histopathological and clinical features, including potentially aggressive behaviour, high recurrence rate, and an association with the nevoid basal cell carcinoma syndrome. The characteristic histologic feature i.e. the presence of parakeratin, is unique amongst all the different inflammatory and developmental cysts that occur in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…The present study, showed an intense p53 expression in OKC when compared with ameloblastoma, which lends support to the new nomenclature for this lesion as Keratocystic odontogenic tumour; warranting the need for more aggressive treatment modality such as enucleation with application of carnoy's solution [26].…”
Section: Resultssupporting
confidence: 84%
“…The present study, showed an intense p53 expression in OKC when compared with ameloblastoma, which lends support to the new nomenclature for this lesion as Keratocystic odontogenic tumour; warranting the need for more aggressive treatment modality such as enucleation with application of carnoy's solution [26].…”
Section: Resultssupporting
confidence: 84%
“…Authors had been shedding light into the importance of careful histological exam in extensive lesions, in order to prevent a poor diagnosis 8 . Thus, a biopsy is the first step in any extended mandibular lesion.…”
Section: Discussionmentioning
confidence: 99%
“…For a while since its first description by Philipsen in 1956 OKC ideal treatment was considered controversial 8 , diverging between conservative and aggressive surgical treatments. Lately, the literature has suggested less invasive interventions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Different studies show different recurrence rates (2,4,33). Most reports show that recurrence will appear with in 5 to 7 years (12,22,27,29).…”
Section: Discussionmentioning
confidence: 99%